1959
DOI: 10.1177/000348945906800411
|View full text |Cite
|
Sign up to set email alerts
|

LXXVI The Lateral Pharyngeal Cleft

Abstract: There is considerable question concerning the boundaries and relations of the lateral pharyngeal cleft. The purpose of this work is to determine the boundaries of this region, its relations with sur rounding spaces, and the existence of any direct communications between the lateral pharyngeal cleft and contiguous spaces. The results are based on the dissection of approximately 3 5 half heads. DESCRIPTION The lateral pharyngeal cleft is enclosed by a definite and discrete fascial boundary. Medially, it is bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Several cadaver dissection studies, some of which have incorporated the injection of colored gelatin, have shown free communication between the submandibular and parapharyngeal spaces . However, other dissection studies and clinical and radiologic observations do not support such a communication…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cadaver dissection studies, some of which have incorporated the injection of colored gelatin, have shown free communication between the submandibular and parapharyngeal spaces . However, other dissection studies and clinical and radiologic observations do not support such a communication…”
Section: Methodsmentioning
confidence: 99%
“…It is commonly described as an inverted pyramid, cone, funnel, or triangle with the skull base superiorly and the greater cornu of the hyoid bone or mandible inferiorly, although this concept has been challenged . Laterally, it is bordered by the medial pterygoid muscle and parotid gland, posteriorly by the prevertebral muscles or carotid sheath (depending on the definition), and medially by the visceral fascia covering the pharyngeal muscles . Some authors subdivide the space into the anterior (prestyloid) and posterior (poststyloid) compartments .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] This complex space is anatomically surrounded by numerous structures [2] and divided by the styloid process into the pre- and post-styloid spaces. [3] The rationale behind this subdivision is that the different structures occupying these subspaces can be the source of various tumors with an anatomic space of origin suggestive of their nature.…”
Section: Introductionmentioning
confidence: 99%
“…17 The area occupied by the stylomandibular fascia has been designated the orifice préstylien by Faure, 12 boutonnière rétrocondylienne by Rouviere, 42 and the stylomandibular tunnel by Patey and Thackray. In this vicinity the stylopharyngeus muscle passes deep to the medial wall and the fascia continues inferi orly to sweep between the posterior border of the stylomandibular membrane and the stylohyoid muscle.…”
mentioning
confidence: 99%